2011
DOI: 10.1039/c0ce00759e
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of icosahedral nickel nanocrystals

Abstract: Nickel nanocrystals with icosahedral morphologies have been successfully synthesised using a microwave-assisted irradiation method. Nickel acetylacetonate was used as the metal precursor, while sodium formate and trioctylphosphine oxide were employed as the reducing agent and capping ligands, respectively. The nanocrystals, with a mean diameter of 237 AE 43 nm, exhibited enhanced ferromagnetic behaviour at room temperature compared to bulk nickel, with coercivities of up to 164 Oe and saturation magnetisation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(48 reference statements)
0
13
0
1
Order By: Relevance
“…Many studies [ 21 23 , 29 31 , 34 , 53 58 ] have reported Ni-based nanomaterials with different structures using different preparation methods, surfactants, reducing agents. Some of them have exhibited good performances in terms of their size and morphology control of the nanostructures, as shown in Table 1 [ 13 , 17 , 21 , 29 31 , 34 , 35 , 53 59 ]. However, the successful routes for fabrication of these nanomaterials have some disadvantages including high cost, poor stability, and complexity.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies [ 21 23 , 29 31 , 34 , 53 58 ] have reported Ni-based nanomaterials with different structures using different preparation methods, surfactants, reducing agents. Some of them have exhibited good performances in terms of their size and morphology control of the nanostructures, as shown in Table 1 [ 13 , 17 , 21 , 29 31 , 34 , 35 , 53 59 ]. However, the successful routes for fabrication of these nanomaterials have some disadvantages including high cost, poor stability, and complexity.…”
Section: Resultsmentioning
confidence: 99%
“…This allows a wide range of experimental parameters and fine control over the growth is available. Although many Ni nanomaterials including NPs, 31,32 nanoflowers, 33 nanochains 6,7,15,25 and NWs, 25,34 have been successfully prepared by the microwave technique, most research focuses on Ni nanostructures with different shapes 22,31,33 or Ni nanowire arrays in templates. 13,14,16,17 However, since grain size, crystallinity, and orientation influence the magnetic properties and catalytic activities, as well as mechanical reliability of NWs, control over microstructure is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Принимая во внимание опыт как проведенных ранее нами исследований [10][11][12], так и опыт различных исследовательских групп [13][14][15][16][17][18][19][20][21], а также обозначенную актуальность получения никелевых покрытий с заданными свойствами, в данной работе представлены результаты экспериментов по получению сплошных никелевых покрытий, содержащих преимущественно микрокристаллы с пентагональной симметрией.…”
Section: Introductionunclassified